The Relationship Between The Level of Maternal Knowledge, Maternal Employment Status and Family Support With Exclusive Breastfeeding in The Working Area of The Air Dingin Health Center of Padang City in 2018 - Dian Hidayah Putri; Masrul Masrul; Lisma Evareny (Journal of Midwifery, 2018)
In order to reduce infant morbidity and mortality, UNICEFand WHO recommend exclusive breastfeeding for six monthsbecause ASI has many health benefits for babies and containsall the nutrients needed by baby. The lowest coverage ofexclusive breastfeeding in Padang City is in the working areaof Puskesmas Air Dingin. The purpose of this study was todetermine the relationship between the level of maternalknowledge, maternal employment status and family supportwith exclusive breastfeeding in the working area of the AirDingin Health Center. Analytic research withdesign was cross sectionalconductedin the working area of Air Dingin Health Center from June2018 to July 2018. The sample in this study were mothers whohad infants aged> 6-12 months as many as 56 people. Mothersas respondents were interviewed directly using a questionnaire.Data analysis was univariate and bivariate usinganalysis chisquare(p5 0.05).The results showed that the percentage of exclusivebreastfeeding was 51.8%. Theanalysis results chi-squareshowed that the p value between exclusive breastfeeding andthe level of maternal knowledge (p = 0.010), maternalemployment status (p = 1,000), and family support (p = 0.021). There was a significant relationship between the level ofmother's knowledge and family support with exclusivebreastfeeding, while the mother's employment status did nothave a significant relationship with exclusive breastfeeding. Itis hoped that mothers can maintain and improve exclusivebreastfeeding.